2012
DOI: 10.1182/blood-2011-11-394395
|View full text |Cite
|
Sign up to set email alerts
|

Mutated regions of nucleophosmin 1 elicit both CD4+ and CD8+ T-cell responses in patients with acute myeloid leukemia

Abstract: Mutations in the nucleophosmin gene (NPM1 mut ) are one of the most frequent molecular alterations in acute myeloid leukemia (AML), and immune responses may contribute to the favorable prognosis of AML patients with NPM1 mut . In the present study, we were able to demonstrate both CD4 ؉ and CD8 ؉ T-cell responses against NPM1 mut . Ten peptides derived from wild-type NPM1 and NPM1 mut were subjected to ELISPOT analysis in 33 healthy volunteers and 27 AML patients.Tetramer assays against the most interesting ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
115
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(121 citation statements)
references
References 31 publications
6
115
0
Order By: Relevance
“…This is reflected by the emergence of antigen-specific CD8 þ T cells in the peripheral blood of AML patients following transplantation. Such CTL responses have been reported against a broad range of AML-related tumor antigens, including HOXA9 (HOXA9 146-154 ), 62 hTERT (hTERT 540-548 ), 62 27,62 and RAGE-1 (RAGE-1 [11][12][13][14][15][16][17][18][19][20] (Table 1). 79 NuSAP1 has been identified as a target of humoral immunity following allogeneic HSCT.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 83%
See 1 more Smart Citation
“…This is reflected by the emergence of antigen-specific CD8 þ T cells in the peripheral blood of AML patients following transplantation. Such CTL responses have been reported against a broad range of AML-related tumor antigens, including HOXA9 (HOXA9 146-154 ), 62 hTERT (hTERT 540-548 ), 62 27,62 and RAGE-1 (RAGE-1 [11][12][13][14][15][16][17][18][19][20] (Table 1). 79 NuSAP1 has been identified as a target of humoral immunity following allogeneic HSCT.…”
Section: Criterion 4: Immunogenicity Humoral and Cellular Immune Respmentioning
confidence: 83%
“…The mutant proteins arising from these gene mutations are known to act as LSAs. [10][11][12] The majority of antigens have been characterized as LAAs, that is, they are expressed by both normal and leukemic cells. Hence, autoimmunity could be a logical consequence of targeting TAAs.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that epitopes derived from the mutated regions of NPM1 induced specific CD4 + and CD8 + T-cell responses. Two HLA-A2 restricted epitopes induced high frequencies of specific CD8 + T-cell responses in healthy volunteers and AML patients [79]. Furthermore, a survival analysis of 25 NPM1 mut patients, comparing cases with or without specific CTL responses against NPM1 mut epitopes, suggested a better overall survival of patients with specific NPM1 mut CTL responses [80].…”
Section: Mutated Epitopes (Neoantigens)mentioning
confidence: 99%
“…Our group previously described specific immune responses against epitopes derived from the mutational region of NPM1. 1 Furthermore, in a smaller cohort of AML patients we found a significantly better overall survival for patients with specific cytotoxic T-lymphocyte (CTL) response against NPM1 mut -derived immunogenic epitopes, 2 when compared to NPM1 wt AML patients. This suggests that immune responses against NPM1 mut might in part contribute to the more favorable outcome in AML patients.…”
mentioning
confidence: 98%